A case of Sacro-Coccygeal Chordoma Mimicking A Pilonidal sinus - Aurangzeb, Mehmud; Sartaj, Farsheed (Journal of Postgraduate Medical Institute, 2011)
Chordoma is a rare, low grade malignant neoplams thought to develop from embryonic remnants of the notochord. Pilonidal sinus disease, characterized by communicating granulating natal cleft tracts and abscesses, is a common condition. We report a case of a sacroccygeal chorodoma diagnosed incidentally on surgical exploration of a case of resumed recurrent pilonidal disease.